The Potential Role of Monocyte Chemoattractant Protein-1 for Major Depressive Disorder - Pae, Chi-Un (Korean Neuropsychiatric Association, 2014)
The immune hypothesis of major depressive disorder (MDD) fits well with the supposed interaction between genetic and environmental factors in disorders with a complicated etiopathogenesis. It has been suggested that infectious diseases are associated with MDD in that cytokines may play a critical role as a key modulator in the transition between infection and the development of MDD. It has been also suggested that antidepressants have immunomodulatory effects on some cytokines and cytokine receptors, although the exact mechanism has not yet been fully elucidated. Among cytokines, monocyte chemoattractant protein-1 (MCP-1) is especially well known and has attracted considerable interest owing to its immunomodulatory functions. MCP-1 is expressed in highly regionalized neuronal areas in the brain, leading to kind of modulation of neuronal activity and neuroendocrine functions commonly seen in patients with MDD. Additionally, it is involved in the control of other cytokines that have been consistently proposed as associated with the development of MDD. It also has a possible role in the neurodegenerative process of a number of central nervous system (CNS) diseases. Hence, this paper draws from the perspective of immunology to offer several suggestions about the role of MPC-1 in the development of MDD.